Schools As Emotional Safe Spaces: Micro-Strategies Of Teacher Intervention In Preventing Public Health Crises - Juniarmi, Intan; Rosmaria, Rosmaria; Rachmawati, Denny Aulia (PT. Anagata Sembagi Education, 2025)
The increasing prevalence of mental health disorders among students has become a structural crisis in the education system, especially in Indonesia which still focuses solely on academic achievement. This study aims to conceptually examine the strategic role of schools and teachers in building an emotional safe space through a micro-intervention approach and the integration of social-emotional dimensions into education policies. Using a descriptive qualitative method with literature studies as the main technique, data were collected from various scientific sources and education policies in the last five years, then analyzed using a thematic content analysis approach. The results of the study indicate that schools that ignore emotional well-being tend to worsen students' psychological distress, while teacher micro-interventions such as emotional validation and restorative approaches have proven effective in increasing mental resilience. Lack of teacher training and the absence of psychosocial intervention standards in the curriculum are major obstacles. This study recommends the need for education policy reform that places Social-Emotional Learning (SEL) as a core competency, as well as strengthening synergy between sectors in supporting students' mental health. Thus, schools can function as emotional safe havens that protect and empower the younger generation in facing current and future psychosocial challenges